EVALUASI MANAJEMEN ASET, ASURANSI DAN DANA PENDIDIKAN ANAK TERHADAP KEKAYAAN BAPAK BANGKIT NUGROHO - , Bhayu Santoso Nugroho; , Prof. Dr. Eduardus tandelilin, MBA, CWM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this study is to provide recommendation regarding the needs of a High Net Worth Individuals in aspects of Insurance, Education Fund, and Asset Management based on three pillars in Wealth Management. The technique performed to determine the client profile is by giving a questionnaire and the result then used as reference in providing recommendations. The recommendations are provided to clients in the form of Sharia PRUlink Assurance Account